Tradisi Beraspati Desa Kembang Kerang Daya - Muhammad Zainul Hasan (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2020)
Theologically from time to time the meaning of alms remains the same, but when it intersects with different traditions and cultures and places, alms will be applied in various ways. In Javanese society many alms practices are carried out, such as earth alms, sea alms, as a form of expression of gratitude, alms as a form to be rejected from reinforcements and so forth. Unlike what is done by the Kembang Kerang Daya community, Lombok, they do alms while doing the medication usually called beraspati. This article will examine how tradition beraspati is run and are there factors of religious texts that motivate patriot tradition. This study was analyzed using Max Weber's theory of action; traditional action, instrumental action, effective action, value rationality action. From the theory of action, the researcher found that the tradition of the beraspati (1)has been carried on from generation to generation, (2)carrying out the tradition consciously and the tradition of the pigeon is the best way to channel alms, (3)shows that the offender has a strong emotional attitude with the healer (physician) thus forming a high confidence, (4)their servitude by surrendering after treatment and with alms they get blessings so that the wounded recover quickly.